An Assessment of Family Based Smart Home Reference Architecture Model - Vivid Theresa Wina; Heru Purnomo Ipung; Tanika D. Sofianti (Syntax Literate, 2022)
The smart home concept is a promising and efficient means of promoting good health, offering comfort and security, and so improving one's quality of life. Despite the advantages of smart home technology, why is adoption so low and not widely embraced by mainstream consumers? Most strategies are based on experimentation or are solely focused on the technological aspects. Technological or engineering perspectives on smart houses have failed to capture the true requirements of future smart home users. Through this research, we will determine the business gap preventing smart home adoption, as well as users' perspectives on smart homes and their concerns regarding smart home technologies. An online survey with 17 participants of household family has been undertaken as part of this research in order to better understand the attitudes and perceptions of potential smart home users, with the results of the survey being analyzed in depth afterwards. The results from this research may help broaden our understanding of the process of adopting smart homes and give valuable insight into user-centered tactics for promoting smart home service adoption.